2011
DOI: 10.1002/aic.12701
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of titania films coated by liquid‐phase deposition on AISI304 stainless steel substrates

Abstract: Fouling deposition and localized corrosion on the heat‐transfer surfaces of the stainless steel equipments often simultaneously exist, which can introduce additional thermal resistance to heat‐transfer and damage heat‐transfer surfaces. It is a good anticorrosion way to coat a barrier layer of certain materials on the metal surface. In this article, the TiO2 coatings with nanoscale thicknesses were obtained by liquid‐phase deposition method on the substrates of AISI304 stainless steel (ASS). The coating thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…To obtain anticipated performance of scale inhibition, various coatings have been well fabricated on heat exchanger plates by selecting suitable surface engineering techniques such as sputter technology for DLC, ion implantation for SiF 3 + , autocatalytic technology for Ni–P–PTFE, SAM for organosilanes, and LPD for TiO 2 (as shown in Figure ). Significantly, most of these techniques have been employed to manage antiscaling property, thereby leading to an increase in the heat transfer coefficient and excellent heat transfer performance in scaling environments…”
Section: The Fabrication Methods Of Antiscaling Coatingmentioning
confidence: 99%
“…To obtain anticipated performance of scale inhibition, various coatings have been well fabricated on heat exchanger plates by selecting suitable surface engineering techniques such as sputter technology for DLC, ion implantation for SiF 3 + , autocatalytic technology for Ni–P–PTFE, SAM for organosilanes, and LPD for TiO 2 (as shown in Figure ). Significantly, most of these techniques have been employed to manage antiscaling property, thereby leading to an increase in the heat transfer coefficient and excellent heat transfer performance in scaling environments…”
Section: The Fabrication Methods Of Antiscaling Coatingmentioning
confidence: 99%
“…[8] TiO 2 nanostructured thin films are also used as various optical coatings for its good transmittance in the visible region, high refractive index and chemical stability. [9,10] In the last two decades, several experimental methods, such as chemical vapor deposition, [11] pulsed laser deposition, [12] sputtering [13] and sol-gel technique, were used for preparation of the TiO 2 nanostructured films. [14][15][16] In comparison with other methods, the sol-gel technique has some advantages such as controllability, reliability and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Among these techniques, coating protection is a promising one and has been studied by several research groups [4,5]. Investigations showed that inorganic coatings such as silica and titania have promising prospects for the corrosion inhibition, relatively low heat resistance and high thermal stability [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…[7]. Magnetron sputtering and vapor deposition methods need complex process and expensive equipment, and it is also difficult to deposit the materials on the substrates with large surface area and irregular shape.…”
Section: Introductionmentioning
confidence: 99%